EVALUASI KEBIJAKAN PENGELOLAAN KAWASAN PANTAI UTARA KABUPATEN BEKASI DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT PESISIR - Danial Thaib (Jurnal Green Growth dan Manajemen Lingkungan, 2012)
ABSTRACTThe objectives of this research are to (i) Evaluate the desired results in the policies concerning spatial planning in North Coast Special Area Bekasi; (ii) analyze the people's views in the framework of the implementation of policies concerning the plan space utilization patterns in the North Coast Special Area Bekasi; and (iii) analyze the positive impact on gross domestic product of policy implementation plan regarding the utilization of space, in the North Coast Special Area Bekasi. This research was conducted in Coastal Areas Bekasi which consists of three districts namely Babelan District, District Tarumajaya, and Muara Gembong District covering an area of 24615.06 ha. Analysis of the data has been obtained from field data collection activities. Examination of the data in this research done by triangulation technique which is based on sources and methods to confirm the interview data, observation, questionnaires and documents. This study concludes, as follow: 1) The authorities in order to prioritize the utilization and management of coastal development Bekasi in the industrial sector; 2) The private sector to give priority to the industrial sector increased employment, achieve optimization ofthe utilization of coastal areas; 3) Community considers that the main priority is the priohty use of the industry, except for the prevention of environmental degradation, conservation, cultural activities and cultural goals to prioritize transportation and tourism, 4) The view NGOs to prioritize the utilization ofthe industryas a major priority in orderto develop the coastal villages Bekasi, and 5) Banking holds to the phority use ofmost ofthe industrial sector. Third, the positive impact the implementation of policies conceming the utilization of space in North Coast Special Area Bekasi to increase gross domestic income can be viewed through the largest contribution to GDP formation Bekasi.